Evaluasi Reaksi Terhadap Pelaksanaan Diklat Penguatan Kepala Sekolah di BPSDM Provinsi DKI Jakarta - Neny Rahmawati (Universitas Mathla'ul Anwar Banten, 2020)
EVALUATION OF THE REACTION TO THE IMPLEMENTATION OF STRENGTHENING SCHOOL PRINCIPAL IN BPSDM DKI JAKARTA PROVINCE. The strategic role of the headmaster in education requires the implementation of the school principal strengthening. This study aims to see the results of the reaction evaluation of the participants of the strengthening school principal, held by the BPSDM DKI Jakarta province with the evaluation model of Kirkpatrick Level 1. The method used is a descriptive evaluative with the survey method. The instruments used are questionnaires. Sampling with a random sampling purpose technique and selected 90 participants from the total population of 900 people. The results showed an average of the participants’ overall response to the faculty evaluation element of 3.61, so it could be stated that the Participants had a very good perception of the whole teacher. The average is obtained because the quality of module and quality of organizers have been good, while the quality of facilities and infrastructure is very good. The conclusion of this research is the response of participants in the implementation of the school's strengthening training (MCC) is very good towards the teacher evaluation element. So also the participants ' response to the quality of the modules and organizers is good, and the response is excellent to the facilities and infrastructure.